ADDED VALUE OF CATECHOLAMINE PHENOTYPING AND GENETIC SCREENING FOR THE CHARACTERIZATION OF PHEOCHROMOCYTOMA: A BELGIAN MULTICENTRE COHORT. (April 2021) - Courcelles, Louisiane; Gruson, Damien; Evenepoel, Lucie; Maiter, Dominique; Persu, Alexandre
Abstract: Objective: Pheochromocytomas/paragangliomas (PPGL) are rare neuroendocrine tumors arising from chromaffin cells of the adrenal medulla or from neural-crest derived sympathetic tissue. They secrete catecholamines in varying amounts, which accounts for their symptomatology. Hypertension is the most common sign, found in approximately 95% of patients. Nowadays, biochemical testing remains the simplest and most widely available method to assess PPGL in first intention. Identification of mutations in known susceptibility genes may help further refining tumor characterization and prognosis assessment. The objective of this study was to analyze clinical characteristics of PPGL from Belgium according to their secretory and genetic profiles. Design and method: We retrospectively analyzed a cohort of 120 cases of non-syndromic PPGL diagnosed in 19 Belgian centres. Clinical characteristics were correlated with three catecholamine phenotypes based on urinary metanephrines (noradrenergic, adrenergic and silent) and with the results of genetic screening. Results: Our cohort included a majority of women (59%). The mean age at diagnosis was 47 ± 7 years. We documented the prevalence of pediatric (7.5%), extra-adrenal (13.3%), bilateral (2.9%), multifocal (5.1%), recurrent (8.5%), metastatic (7.6%) and familial (5.9%) cases. While the yield of positive genetic screening was low (15%), the presence of at least one of these criteria was associated with a 4-fold increased prevalence of mutation (30.3 vs 8.5%; p = 0.03). In the subset in whom metanephrines values were available (n = 62), the prevalence of adrenergic, noradrenergic and silent phenotypes was 58%, 34% and 8% respectively. Patients belonging to these three subsets differed by age at diagnosis (51 ± 14; 38 ± 17; 42 ± 13 years; p = 0.009), the proportion of extra-adrenal tumors (2.8%; 9.5%; 40%; p = 0.016), pediatric (2.8%; 19%; 0%; p = 0.074) and familial (0%; 18.8%; 0%; p = 0.041) cases. Finally, an excess of dopamine secretion was associated with a higher prevalence of metastatic disease (25% vs 1.9%; p = 0.005). Conclusions: Secretory phenotypes and genetic profiles deserve to be integrated in the preoperative characterization of PPGL and may help orienting management and follow-up. Simple clinical features are associated with an increased probability of inherited tumor. Identification of an increased dopamine secretion should raise the suspicion of metastatic PPGL.